1988
DOI: 10.1007/bf02432939
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of natural forest dieback based on the “pipe model” analogy

Abstract: A decade of investigation of stand-level dieback of Metrosideros in the Hawaiian montane rain forests has led to the theory that one of the major underlying causes is cohort senescence. A literature review shows that while there is little evidence of a senescence mechanism in polycarpic trees, the low vigor associated with the senescent state is correlated with a declining balance of photosynthesis to respiration. Specific Leaf Burden (SLB, cm 3 of sapwood per g of leaf mass) is here defined as an index of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This continuation of dieback until virtually every tree is affected is evidence that tree mortality in these relev6s is not density dependent. This finding is in agreement with the results of a field experiment which showed that thinning an '6hi'a stand did not reduce the mortality rate of canopy trees in three different sites with symptoms of dryland dieback (Gerrish et al 1988). In contrast to the five relev6s that advanced into more extreme dieback classes, six others remained in Tab 1 Description of five forest vigor classes, based on the dieback index calculated for each relev6.…”
Section: Changes In Canopy Tree Vigor Between 1977 and 1986supporting
confidence: 85%
“…This continuation of dieback until virtually every tree is affected is evidence that tree mortality in these relev6s is not density dependent. This finding is in agreement with the results of a field experiment which showed that thinning an '6hi'a stand did not reduce the mortality rate of canopy trees in three different sites with symptoms of dryland dieback (Gerrish et al 1988). In contrast to the five relev6s that advanced into more extreme dieback classes, six others remained in Tab 1 Description of five forest vigor classes, based on the dieback index calculated for each relev6.…”
Section: Changes In Canopy Tree Vigor Between 1977 and 1986supporting
confidence: 85%
“…The increasing difference between the requirements for water and the costs of drawing it from the soil and supplying it for the leaves which increases with tree size, is probably one of the reasons of growth deceleration and plant senescence. Tree senescence can be seen as an inescapable result of continuous growth rather than a phase or special mechanism that has been favoured in the population by natural selection (Gerrish 1988). The relative area of sapwood in Norway spruce is to a significantly lesser degree (R 2 = 0.70) determined by a and I r if compared to sapwood width or area in absolute measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, sapwood volume enlarges exponentially with the leaf area growth, accompanied by a proportionate increase of maintenance respiration (Ryan 1989). The tree's normal growth results in decline in the ratio of photosynthetic to respiring tissues (Valentine 1985;Mäkelä 1986;Gerrish 1988). From a certain size of the tree onwards, the growing respiration costs begin to limit the further increase of sapwood, and some time later, the growth of the whole tree.…”
Section: Introductionmentioning
confidence: 97%
“…Pronounced shifts in tree growth patterns occur over short distances: growth of spruce on mesic sites is positively correlated with warm summer temperatures, but on xeric sites it is correlated with cool, wet summers . Many western conifers also live longer on xeric sites, partly from lack of disturbance, but apparently also for physiological reasons (Schulman 1954, Gerrish 1988. Thus, pioneer limber pines in the subalpine zone might be replaced more slowly on xeric sites simply because they tend to live longer there.…”
Section: Introductionmentioning
confidence: 99%